39AR-40AR EVIDENCE FOR EARLY IMPACT EVENTS ON THE LL PARENT BODY - Dixon E.T.; Bogard D.D.; Garrison D.H.; Rubin A.E. (My University, 2004)
We determined 39Ar- 40Ar ages of eight LL chondrites, and one igneous inclusion from an LL chondrite, with the object of understanding the thermal history of the LL-chondrite parent body. The meteorites in this study have a range of petrographic types from LL3.3 to LL6, and shock stages from S1 to S4. These meteorites reveal a range of K-Ar ages from ≥3.66 to ≥4.50 Ga, and peak ages from ≥3.74 to ≥4.55 Ga. Significantly, three of the eight chondrites (LL4, 5, 6) have K-Ar ages of ˜4.27 Ga. One of these (MIL99301) preserves an 39Ar- 40Ar age of 4.23 ± 0.03 Ga from low-temperature extractions, and an older age of 4.52 ± 0.08 Ga from the highest temperature extractions. In addition, an igneous-textured impact melt DOM85505,22 has a peak 39Ar- 40Ar age of ≥4.27 Ga. We interpret these results as evidence for impact events that occurred at about 4.27 Ga on the LL parent body that produced local impact melts, reset the 39Ar- 40Ar ages of some meteorites, and exhumed (or interred) others, resulting in a range of cooling ages. The somewhat younger peak age of 3.74 Ga from GRO95658 (LL3.3) suggests an additional impact event close to timing of impact-reset ages of some other ordinary chondrites between 3.6-3.8 Ga. The results from MIL99301 suggest that some apparently unshocked (S1) chondrites may have substantially reset 39Ar- 40Ar ages. A previous petrographic investigation of MIL99301 suggested that reheating to temperatures less than or equal to type 4 petrographic conditions (600°C) caused fractures in olivine to anneal, resulting in a low apparent shock stage of S1 (unshocked). The 39Ar- 40Ar age spectrum of MIL99301 is consistent with this interpretation. Older ages from high-T extractions may date an earlier impact event at 4.52 ± 0.08 Ga, whereas younger ages from lower-T extractions date a later impact event at 4.23 ± 0.03 Ga that may have caused annealing of feldspar and olivine.